Faktor penentu keputusan pembelian dengan kepercayaan merek sebagai variabel intervening pada kosmetik halal - Anjelina, Novita; Andni, Riyan (MBR (Management and Business Review), 2024)
The increasing popularity of halal cosmetics among students who consume The Originote products, a well-known brand in Indonesia, is the driving force for this research. The aim of this research is to determine the influence of brand awareness, religiosity, halal labels, and E-WOM through brand trust on purchasing decisions. 123 respondents from Kudus City residents who use Originote cosmetics are the sample size in this quantitative research. Partial Least Square (PLS), which is a variance-based Structural Equation Modeling (SEM) approach, is used in the analysis of this research. These findings show how brand awareness and E-WOM can be strongly mediated in purchasing decisions through brand trust variables. However, there is no visible mediating effect of brand trust in halal labels and religiosity on purchasing decisions.